Standardizing Spatial Reconstruction Parameters for the Atom Probe Analysis of Common Minerals - Fougerouse, Denis; Saxey, David; Rickard, William; Reddy, Steven; Verberne, R. (CAMBRIDGE UNIV PRESS, 2022)
Well-defined reconstruction parameters are essential to quantify the size, shape, and distribution of nanoscale features in atom probe tomography (APT) datasets. However, the reconstruction parameters of many minerals are difficult to estimate because intrinsic spatial markers, such as crystallographic planes, are not usually present within the datasets themselves. Using transmission and/or scanning electron microscopy imaging of needle-shaped specimens before and after atom probe analysis, we test various approaches to provide best-fit reconstruction parameters for voltage-based APT reconstructions. The results demonstrate that the length measurement of evaporated material, constrained by overlaying pre-and post-analysis images, yields more consistent reconstruction parameters than the measurement of final tip radius. Using this approach, we provide standardized parameters that may be used in APT reconstructions of 11 minerals. The adoption of standardized reconstruction parameters by the geoscience APT community will alleviate potential problems in the measurement of nanoscale features (e.g., clusters and interfaces) caused by the use of inappropriate parameters.